2020
DOI: 10.3892/ol.2020.12117
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value and clinical significance of circulating miR‑650 and CA211 in detecting of gastric carcinoma

Abstract: The present study determined the levels of plasma biomarkers in patients with gastric carcinoma (GC) and investigated their clinical significance and diagnostic value. Between April 2014 and December 2018, 90 patients with GC, 90 patients with precancerous lesions (Pre) and 45 healthy controls (NC) were recruited from the Affiliated Liutie Central Hospital of Guangxi Medical University. Five markers were measured: microRNA-650 (miRNA-650; using reverse transcription-quantitative polymerase chain reaction), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Combinations of biomarkers, such as circulating miR-19a-3p and miR-483-5p, can enhance the diagnostic performance in various cancer types (59)(60)(61)(62). Notably, Chen et al (18) recently demonstrated that miR-650 combined with CA211 could be an effective diagnostic indicator for screening of the incidence of GC. Sun et al (63) demonstrated that the combination of serum multi-dimensional biomarkers could further improve the specificity and sensitivity of GC detection, thus achieving higher diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of biomarkers, such as circulating miR-19a-3p and miR-483-5p, can enhance the diagnostic performance in various cancer types (59)(60)(61)(62). Notably, Chen et al (18) recently demonstrated that miR-650 combined with CA211 could be an effective diagnostic indicator for screening of the incidence of GC. Sun et al (63) demonstrated that the combination of serum multi-dimensional biomarkers could further improve the specificity and sensitivity of GC detection, thus achieving higher diagnostic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that the combination of miR-650 and CA211 can distinguish between benign and malignant GC ( 18 ). Therefore, we hypothesized that the combined assessment of miRNAs and blood routine parameters may reveal novel insights for the diagnosis of GC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it could modulate oxaliplatin resistance via the miR-129-5p/ETV1 axis in HCC, indicating a promising strategy for combating HCC chemotherapy resistance (18). Currently, endoscopy and biopsy are the standard diagnostic approaches for GC, and their utility is confined to the invasiveness of the disease and limited medical resources (84). Jiang et al (29) assessed PCGEM1 expression in GC patient serum and found that it could reflect the pathophysiological state of GC (29), demonstrating that this molecule might be a favorable indicator for GC diagnosis and prognosis.…”
Section: Clinical Prospects Of Pcgem1mentioning
confidence: 99%
“…For example, it could modulate oxaliplatin resistance via the miR-129-5p/ETV1 axis in HCC, indicating a promising strategy for combating HCC chemotherapy resistance ( 18 ). Currently, endoscopy and biopsy are the standard diagnostic approaches for GC, and their utility is confined to the invasiveness of the disease and limited medical resources ( 84 ). Jiang et al.…”
Section: Clinical Prospects Of Pcgem1mentioning
confidence: 99%
“…However, gastroscopy consumes tremendous medical resources, and its cost-benefit remains debatable. Besides, because of its invasiveness, gastroscopy causes great anxiety to the subjects (7,8). Therefore, current screening strategies only cover high-risk individuals who are older than 40 years or those with a prior history of gastropathy (9).…”
Section: Introductionmentioning
confidence: 99%